Antibacterial high-toughness PP plastic and preparation method

By using alumina carriers to load curcumin in PP plastics and through specific chemical coating and grafting reactions, the problem of PP plastic breeding bacteria in humid environments is solved, and the stability and antibacterial properties of curcumin are improved, achieving high toughness and strong antibacterial PP plastics.

CN119039703BActive Publication Date: 2025-04-08JIEYANG YUANMEI PLASTIC IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411384480.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-08
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Ordinary PP plastics are prone to breed bacteria in humid and high-temperature environments, and curcumin has poor solubility in water, insufficient chemical stability, low bioavailability, too fast metabolic speed and susceptible to photodegradation.

Method used

Curcumin is supported by loading curcumin with alumina as a support and combining p-methoxycinnamaldehyde with glycine to form a compound, curcumin and alumina are coated so that it can be grafted with ferulic acid and connected with polypropylene in the form of chemical bonds, improving the stability and antibacterial properties of curcumin.

Benefits of technology

It improves the stability and antibacterial properties of curcumin, enhances the antibacterial ability of PP plastic, and improves its tensile strength and toughness properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an antibacterial high-toughness PP plastic and a preparation method, and belongs to the technical field of PP plastics. An antibacterial high-toughness PP plastic comprises the following components: polypropylene, styrene-maleic anhydride copolymer, a composite antibacterial agent, an antioxidant, a light stabilizer, a heat stabilizer, an initiator and a solvent; the preparation of the composite antibacterial agent comprises: obtaining prefabricated particles with aluminum oxide and curcumin, adding glycine and p-methoxycinnamaldehyde to obtain an intermediate, and grafting the intermediate with ferulic acid to obtain a composite antibacterial agent. The present invention uses aluminum oxide as a carrier to load curcumin, and then forms a compound by combining p-methoxycinnamaldehyde with glycine, and coating curcumin and aluminum oxide so that it can be grafted with ferulic acid while also being connected to polypropylene in the form of a chemical bond, so that the stability of curcumin is improved and has stronger antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PP plastics and relates to an antibacterial high-toughness PP plastic and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a common thermoplastic with good chemical stability, heat resistance and mechanical strength. However, ordinary PP plastics are prone to breed bacteria during use, especially in humid and high temperature environments. In order to overcome this problem, researchers have developed antibacterial PP plastics. By adding antibacterial agents such as silver ions and organic antibacterial agents to PP materials, their antibacterial properties can be significantly improved. Antibacterial PP plastics are widely used in medical and health, food packaging, daily necessities and other fields, providing more safety guarantees for people's lives.

[0003] Curcumin is a natural active polyphenol compound, which is mainly found in the rhizomes of ginger plants such as turmeric, turmeric, and zedoary, as well as the rhizomes of araceae plants such as calamus. Curcuminoids mainly exist in the form of curcumin, demethylcurcumin, and bisdemethylcurcumin, and the structures of these compounds are similar to each other. They have a melting point of 183°C and are insoluble in water, but are easily soluble in alkali solutions or organic solvents such as ethanol and acetone. Curcumin is sensitive to pH and is relatively stable in acidic environments, while its decomposition rate is high in neutral or alkaline environments. The various biological activities exhibited by curcumin indicate that it has great application potential in many industries such as food, medicine, and health products. However, the problems of poor solubility in water, insufficient chemical stability, low bioavailability, rapid metabolism, and susceptibility to photodegradation urgently need to be properly addressed. Summary of the invention

[0004] The object of the present invention is to provide an antibacterial high-toughness PP plastic and a preparation method thereof. The present invention uses alumina as a carrier to load curcumin, and then forms a compound by combining p-methoxycinnamaldehyde with glycine, and then coats the curcumin and alumina so that the curcumin can be grafted with ferulic acid and connected with polypropylene in the form of a chemical bond. The stability of the curcumin is improved, and the curcumin has stronger antibacterial performance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An antibacterial high-toughness PP plastic comprises the following components by weight:

[0007] 100-110 parts of polypropylene, 12-15 parts of styrene-maleic anhydride copolymer, 5-8 parts of composite antibacterial agent, 0.1-2 parts of antioxidant, 0.2-0.4 parts of light stabilizer, 0.2-0.4 parts of heat stabilizer, 0.2-0.3 parts of initiator and 10-15 parts of solvent.

[0008] As a preferred technical solution of the present invention, the initiator is one or more of di-tert-butyl peroxide, di-tert-amyl peroxide, diisopropylbenzene peroxide and benzoyl peroxide.

[0009] As a preferred technical solution of the present invention, the antioxidant is one or both of antioxidant 1010 and antioxidant 1076.

[0010] As a preferred technical solution of the present invention, the light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP; and the solvent is white oil.

[0011] The invention discloses a method for preparing the composite antibacterial agent, comprising the following steps:

[0012] 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles;

[0013] 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate;

[0014] 3) placing the intermediate in anhydrous ethanol, stirring and dispersing it, adding ferulic acid and an initiator, heating it, filtering out the solid, washing it, and drying it to obtain a composite antibacterial agent.

[0015] As a preferred technical solution of the present invention, in step 1), the stirring and mixing is stirring at a speed of 300-400 r / min for 10-20 min.

[0016] As a preferred technical solution of the present invention, in step 1), the ultrasonic treatment is performed at a frequency of 1000-1200W for 30-45min.

[0017] As a preferred technical solution of the present invention, in step 1), the washing is performed 3 times using anhydrous ethanol.

[0018] As a preferred technical solution of the present invention, in step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 10-13:40-50:2.0-2.6.

[0019] As a preferred technical solution of the present invention, in step 1), the alumina is γ-alumina;

[0020] As a preferred technical solution of the present invention, in step 2), the heating and stirring is stirring at a temperature of 45-60° C. for 6-8 hours.

[0021] As a preferred technical solution of the present invention, in step 2), the washing is performed 3 times using anhydrous ethanol.

[0022] As a preferred technical solution of the present invention, in step 2), the drying is performed by placing the mixture in an oven at a temperature of 80-90° C. and drying the mixture to a constant weight.

[0023] As a preferred technical solution of the present invention, in step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 6-8:30-40:1.2-1.5:2.3-3.2.

[0024] As a preferred technical solution of the present invention, in step 3), the stirring and dispersing time is 30-40 minutes; the heating treatment is heating at 60-70°C for 5-6 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying to constant weight at 80°C; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 16-18:26-34:2.4-3.2:0.10-0.12; and the initiator is initiator ABIN.

[0025] The invention discloses a preparation method of an antibacterial high-toughness PP plastic. The preparation method comprises the following steps: mixing various raw materials, placing them in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain the antibacterial high-toughness PP plastic.

[0026] As a preferred technical solution of the present invention, the melt extrusion parameters are: a rotation speed of 100-150 r / min and a temperature of 190-220°C.

[0027] Beneficial effects of the present invention:

[0028] The present invention uses alumina as a carrier to load curcumin, and then forms a compound by combining p-methoxycinnamaldehyde with glycine, and coats the curcumin and alumina, so that the curcumin can be grafted with ferulic acid and connected with polypropylene (PP) plastic in the form of chemical bonds, thereby improving the stability of the curcumin and having stronger antibacterial properties.

[0029] The present invention loads curcumin on alumina and forms an organic coating on it with p-methoxycinnamaldehyde, glycine and ferulic acid, thereby increasing the dispersibility of alumina in the system and introducing a hydrophobic benzene ring structure, thereby increasing its binding force with the PP plastic system and increasing its compatibility, and effectively improving the tensile strength of the PP plastic and imparting better toughness performance. DETAILED DESCRIPTION

[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0031] Example 1

[0032] An antibacterial high-toughness PP plastic comprises the following components by weight:

[0033] 100 parts of polypropylene, 12 parts of styrene-maleic anhydride copolymer, 5 parts of composite antibacterial agent, 0.1 parts of antioxidant, 0.2 parts of light stabilizer, 0.2 parts of heat stabilizer, 0.2 parts of initiator and 10 parts of solvent; the initiator is di-tert-butyl peroxide; the antioxidant is antioxidant 1010; the light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP; the solvent is white oil;

[0034] The preparation of the composite antibacterial agent comprises the following steps:

[0035] 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles;

[0036] 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate;

[0037] 3) placing the intermediate in anhydrous ethanol, stirring and dispersing it, adding ferulic acid and an initiator, heating it, filtering out the solid, washing it, and drying it to obtain a composite antibacterial agent.

[0038] In step 1), the stirring and mixing is stirring at a speed of 300 r / min for 10 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 1000 W for 30 min; and the washing is washing with anhydrous ethanol for 3 times;

[0039] In step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 10:40:2.0; the aluminum oxide is γ-aluminum oxide;

[0040] In step 2), the heating and stirring is stirring at 45° C. for 6 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying in an oven at 80° C. to constant weight.

[0041] In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 6:30:1.2:2.3.

[0042] In step 3), the stirring and dispersing time is 30 minutes; the heating treatment is heating at 60°C for 5 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying at 80°C to constant weight; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 16:26:2.4:0.10; and the initiator is initiator ABIN.

[0043] A method for preparing an antibacterial high-toughness PP plastic comprises the following steps:

[0044] The raw materials are mixed and kneaded, and then placed in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain an antibacterial high-toughness PP plastic; the melt extrusion parameters are a speed of 100 r / min and a temperature of 190°C.

[0045] Example 2

[0046] An antibacterial high-toughness PP plastic comprises the following components by weight:

[0047] 103 parts of polypropylene, 13 parts of styrene-maleic anhydride copolymer, 6 parts of composite antibacterial agent, 0.7 parts of antioxidant, 0.27 parts of light stabilizer, 0.27 parts of heat stabilizer, 0.23 parts of initiator and 12 parts of solvent; the initiator is di-tert-butyl peroxide; the antioxidant is antioxidant 1010; the light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP; the solvent is white oil;

[0048] The preparation of the composite antibacterial agent comprises the following steps:

[0049] 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles;

[0050] 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate;

[0051] 3) placing the intermediate in anhydrous ethanol, stirring and dispersing it, adding ferulic acid and an initiator, heating it, filtering out the solid, washing it, and drying it to obtain a composite antibacterial agent.

[0052] In step 1), the stirring and mixing is stirring at a speed of 330 r / min for 15 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 1060 W for 35 min; the washing is washing with anhydrous ethanol for 3 times;

[0053] In step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 11:43:2.2; the aluminum oxide is γ-aluminum oxide;

[0054] In step 2), the heating and stirring is stirring at 50° C. for 6.5 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying in an oven at 83° C. to constant weight.

[0055] In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 6.7:33:1.3:2.6.

[0056] In step 3), the stirring and dispersing time is 32 minutes; the heating treatment is heating at 62°C for 5.2 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying at 80°C to constant weight; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 16.5:28:2.6:0.11; and the initiator is initiator ABIN.

[0057] A method for preparing an antibacterial high-toughness PP plastic comprises the following steps:

[0058] The raw materials are mixed and kneaded, and then placed in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain an antibacterial high-toughness PP plastic; the melt extrusion parameters are a speed of 110 r / min and a temperature of 200°C.

[0059] Example 3

[0060] An antibacterial high-toughness PP plastic comprises the following components by weight:

[0061] 107 parts of polypropylene, 14 parts of styrene-maleic anhydride copolymer, 7 parts of composite antibacterial agent, 1.4 parts of antioxidant, 0.35 parts of light stabilizer, 0.35 parts of heat stabilizer, 0.25 parts of initiator and 13 parts of solvent; the initiator is di-tert-butyl peroxide; the antioxidant is antioxidant 1010; the light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP; the solvent is white oil;

[0062] The preparation of the composite antibacterial agent comprises the following steps:

[0063] 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles;

[0064] 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate;

[0065] 3) placing the intermediate in anhydrous ethanol, stirring and dispersing it, adding ferulic acid and an initiator, heating it, filtering out the solid, washing it, and drying it to obtain a composite antibacterial agent.

[0066] In step 1), the stirring and mixing is stirring at a speed of 360 r / min for 15 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 1130 W for 40 min; and the washing is washing with anhydrous ethanol for 3 times;

[0067] In step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 12:47:2.4; the aluminum oxide is γ-aluminum oxide;

[0068] In step 2), the heating and stirring is stirring at 55° C. for 7.5 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying in an oven at 87° C. to constant weight.

[0069] In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 7.5:37:1.4:2.8.

[0070] In step 3), the stirring and dispersing time is 30-40 minutes; the heating treatment is heating at 66°C for 5.6 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying to constant weight at 80°C; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 17:30:2.8:0.11; and the initiator is initiator ABIN.

[0071] A method for preparing an antibacterial high-toughness PP plastic comprises the following steps:

[0072] The raw materials are mixed and kneaded, and then placed in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain an antibacterial high-toughness PP plastic; the melt extrusion parameters are a speed of 135 r / min and a temperature of 210°C.

[0073] Example 4

[0074] An antibacterial high-toughness PP plastic comprises the following components by weight:

[0075] 110 parts of polypropylene, 15 parts of styrene-maleic anhydride copolymer, 8 parts of composite antibacterial agent, 2 parts of antioxidant, 0.4 parts of light stabilizer, 0.4 parts of heat stabilizer, 0.3 parts of initiator and 15 parts of solvent; the initiator is di-tert-butyl peroxide; the antioxidant is antioxidant 1010; the light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP; the solvent is white oil;

[0076] The preparation of the composite antibacterial agent comprises the following steps:

[0077] 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles;

[0078] 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate;

[0079] 3) placing the intermediate in anhydrous ethanol, stirring and dispersing it, adding ferulic acid and an initiator, heating it, filtering out the solid, washing it, and drying it to obtain a composite antibacterial agent.

[0080] In step 1), the stirring and mixing is stirring at a speed of 400 r / min for 20 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 1200 W for 45 min; the washing is washing with anhydrous ethanol for 3 times;

[0081] In step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 13:50:2.6; the aluminum oxide is γ-aluminum oxide;

[0082] In step 2), the heating and stirring is stirring at 60° C. for 8 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying in an oven at 90° C. to constant weight.

[0083] In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 8:40:1.5:3.2.

[0084] In step 3), the stirring and dispersing time is 40 minutes; the heating treatment is heating at 70°C for 6 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying to constant weight at 80°C; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 18:34:3.2:0.12; and the initiator is initiator ABIN.

[0085] A method for preparing an antibacterial high-toughness PP plastic comprises the following steps:

[0086] The raw materials are mixed and kneaded, and then placed in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain an antibacterial high-toughness PP plastic; the melt extrusion parameters are a speed of 150 r / min and a temperature of 220°C.

[0087] Comparative Example 1

[0088] Compared with Example 2, the difference in Comparative Example 1 is that curcumin is not added in step 1), and curcumin is added in step 2);

[0089] Step 2) After mixing the prefabricated particles, anhydrous ethanol and glycine, p-methoxycinnamaldehyde is added, heated and stirred, solids are filtered out, washed and dried, and curcumin is added and stirred to obtain a composite antibacterial agent;

[0090] The remaining components, preparation steps and parameters were the same.

[0091] Comparative Example 2

[0092] Compared with Example 2, the difference of Comparative Example 2 is that cinnamaldehyde is used instead of p-methoxycinnamaldehyde, and the other components, preparation steps and parameters are the same.

[0093] Comparative Example 3

[0094] Compared with Example 2, Comparative Example 3 is different in that p-methoxycinnamaldehyde is not added, and the remaining components, preparation steps and parameters are the same.

[0095] Comparative Example 4

[0096] Compared with Example 2, Comparative Example 4 is different in that glycine is not added, and the remaining components, preparation steps and parameters are the same.

[0097] Comparative Example 5

[0098] Compared with Example 2, Comparative Example 5 is different in that no ferulic acid is added, and the other components, preparation steps and parameters are the same.

[0099] The PP plastics prepared in Examples 1-4 and Comparative Examples 1-5 were tested as follows, and the test results are shown in Table 1.

[0100] Antibacterial performance test: according to GB / T31402-2015;

[0101] Table 1

[0102] Staphylococcus aureus (%) Escherichia coli (%) Example 1 99.3 99.7 Example 2 99.4 99.8 Example 3 99.1 99.5 Example 4 99.0 99.4 Comparative Example 1 83.5 84.4 Comparative Example 2 86.6 87.6 Comparative Example 3 81.9 82.3 Comparative Example 4 84.2 85.8 Comparative Example 5 86.1 87.7

[0103] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the PP plastics prepared in Examples 1-4 of the present invention have excellent antibacterial properties. The invention uses alumina as a carrier to load curcumin, and the curcumin enters the pore structure of the alumina, thereby reducing the thermal degradation of the curcumin and increasing the stability of the curcumin. Then, p-methoxycinnamaldehyde is combined with glycine to form a chemical structure connected by an imine bond, wherein the methoxy group can give p-methoxycinnamaldehyde better antibacterial performance and can also promote the combination of p-methoxycinnamaldehyde and glycine through hydrogen bonds. The curcumin and alumina are coated, and the stability of the curcumin is further improved. In addition, the compound formed by glycine / p-methoxycinnamaldehyde is more likely to release active hydrogen and combine with free radicals, destroy the metabolism of bacteria by destroying cell membranes and inhibiting the ATP activity of cells, and has stronger antibacterial performance. A part of the introduced carbon-carbon double bonds can be grafted with ferulic acid to improve the stability of ferulic acid and enable the composite antibacterial agent to have a better antibacterial effect. The remaining double bonds can also be connected with polypropylene in the form of chemical bonds, so that the polypropylene macromolecular chain has a stronger and more stable antibacterial structure.

[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An antibacterial high-toughness PP plastic, characterized in that: The components include the following by weight: Polypropylene 100-110 parts, styrene-maleic anhydride copolymer 12-15 parts, composite antibacterial agent 5-8 parts, antioxidant 0.1-2 parts, light stabilizer 0.2-0.4 parts, heat stabilizer 0.2-0.4 parts, initiator 0.2-0.3 parts and solvent 10-15 parts; wherein the solvent is white oil; The preparation of the composite antibacterial agent comprises the following steps: 1) placing alumina in anhydrous ethanol and stirring to mix, adding curcumin and ultrasonically treating, filtering out solids, washing, and freeze-drying to obtain prefabricated particles; 2) mixing the prefabricated particles, anhydrous ethanol and glycine, adding p-methoxycinnamaldehyde, heating and stirring, filtering out the solid, washing and drying to obtain an intermediate; 3) placing the intermediate in anhydrous ethanol, stirring and dispersing, adding ferulic acid and an initiator, heating, filtering out the solid, washing, and drying to obtain a composite antibacterial agent, The alumina is γ-alumina.

2. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: The initiator is one or more of di-tert-butyl peroxide, di-tert-amyl peroxide, diisopropylbenzene peroxide and benzoyl peroxide.

3. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: The antioxidant is one or both of antioxidant 1010 and antioxidant 1076.

4. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: The light stabilizer is UV-9; the heat stabilizer is heat stabilizer DLTP.

5. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: In step 1), the stirring and mixing is stirring at a speed of 300-400 r / min for 10-20 min; the ultrasonic treatment is ultrasonic treatment at a frequency of 1000-1200 W for 30-45 min; and the washing is washing 3 times with anhydrous ethanol.

6. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: In step 1), the mass ratio of the aluminum oxide, anhydrous ethanol and curcumin is 10-13:40-50:2.0-2.

6.

7. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: In step 2), the heating and stirring is stirring at a temperature of 45-60° C. for 6-8 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying in an oven at a temperature of 80-90° C. to constant weight.

8. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, glycine and p-methoxycinnamaldehyde is 6-8:30-40:1.2-1.5:2.3-3.

2.

9. The antibacterial high-toughness PP plastic according to claim 1, characterized in that: In step 3), the stirring and dispersing time is 30-40 minutes; the heating treatment is heating at 60-70°C for 5-6 hours; the washing is washing 3 times with anhydrous ethanol; the drying is drying to constant weight at 80°C; the mass ratio of the intermediate, anhydrous ethanol, ferulic acid and initiator is 16-18:26-34:2.4-3.2:0.10-0.12; and the initiator is initiator AIBN.

10. A method for preparing the antibacterial high-toughness PP plastic according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: mixing the raw materials, placing them in a twin-screw extruder for melt extrusion, pelletizing, and molding to obtain an antibacterial high-toughness PP plastic; the melt extrusion parameters are 100-150r / min rotation speed and 190-220°C temperature.

Citation Information

Patent Citations

  • Preparation method of 4-methoxy-cinnamaldehyde thiosemicarbazone

    CN102702058A

  • Cinnamaldehyde glycine Schiff base and preparation method thereof

    CN117209397A